Liquid crystalline polyester, method for producing liquid crystalline polyester, pellet, and molded product
The formulation of LCP with controlled molecular weight distribution and monomer units addresses the fluidity and mechanical strength issues, enabling its use in diverse molded products with enhanced heat resistance and processing.
Patent Information
- Application Number
- JP2023118230
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
AI Technical Summary
Existing liquid crystal polyester (LCP) formulations lack compatibility with good fluidity during melting and excellent mechanical characteristics, limiting their application in diverse parts and components.
The LCP is formulated with specific molecular weight distribution parameters, including a peak position (g) between 4.50 and 4.87, a peak top Log (M) value between 5.05 and 5.30, and a weight average molecular weight between 100,000 and 2,500,000, incorporating monomer units with condensed aromatic rings and benzene rings, and balanced high and low molecular weight chains.
The LCP exhibits enhanced fluidity during melting and superior mechanical characteristics, making it suitable for a wide range of molded products with improved heat resistance and processing capabilities.
Smart Images

Figure 2025015094000011 
Figure 2025015094000001 
Figure 2025015094000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a liquid crystalline polyester, a method for producing a liquid crystalline polyester, pellets, and a molded article. [Background technology]
[0002] Liquid crystal polyesters are used in a variety of applications due to their high fluidity, heat resistance and dimensional accuracy.
[0003] For example, Patent Document 1 describes a liquid crystal polymer composition containing 15% by mass or more of specific flat glass fibers and 20% by mass or more of a specific plate-like filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-268252 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for improving the properties of liquid crystalline polyesters themselves in order to expand their applications to more diverse uses and to apply them to more precise parts.
[0006] An object of the present disclosure is to provide a liquid crystal polyester that can achieve both good fluidity during melting and excellent mechanical properties of a molded article. Another object of the present disclosure is to provide a method for producing the liquid crystal polyester, and pellets and molded articles containing the liquid crystal polyester. [Means for solving the problem]
[0007] The present disclosure provides, for example: [1] The peak position (G) calculated by the formula (1) is 4.50 or more and 4.87 or less, A liquid crystal polyester in which the peak top of the molecular weight distribution curve is 5.05 or more in terms of log(M) value.
Number
Number
[10] A first liquid crystal polyester having a first molecular weight distribution curve; a second liquid crystal polyester having a second molecular weight distribution curve; Including, the log(M) value of the peak top of the first molecular weight distribution curve is smaller than the log(M) value of the peak top of the second molecular weight distribution curve; The liquid crystal polyester according to any one of [1] to [9].
[11] A method for producing the liquid crystal polyester according to any one of [1] to
[10] , A method for producing a liquid crystalline polyester, comprising the step of mixing two or more liquid crystalline polyesters.
[12] the step of mixing a first liquid crystal polyester having a first molecular weight distribution curve and a second liquid crystal polyester having a second molecular weight distribution curve, the log(M) value of the peak top of the first molecular weight distribution curve is smaller than the log(M) value of the peak top of the second molecular weight distribution curve; The manufacturing method described in
[11] .
[13] A pellet comprising the liquid crystal polyester according to any one of [1] to
[10] .
[14] A molded article comprising the liquid crystal polyester according to any one of [1] to
[10] , The molded article is a connector, a socket, a relay part, a coil bobbin, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a home electrical appliance part, a lighting fixture part, an audio product part, a ferrule for an optical cable, a telephone part, a facsimile part, a modem part, a separation claw, a heater holder, an impeller, a fan gear, a gear, a bearing, a motor part, a motor case, an engine part, an engine room part, an electrical component part, an automobile interior part, a microwave cooking pot, a heat-resistant tableware, a flooring material, a wall material, a beam, a pillar, a roofing material, an aircraft part, a spacecraft part, a space equipment part, a nuclear reactor, an offshore facility member, a cleaning tool, an optical equipment part, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment part, a medical material, a sensor part, a sanitary fixture, a sporting goods, or a leisure goods. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a liquid crystalline polyester that can achieve both good fluidity during melting and excellent mechanical properties of a molded article. In addition, according to the present disclosure, it is possible to provide a method for producing the polyester, and pellets and molded articles containing the liquid crystalline polyester. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram showing a molecular weight distribution curve in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Preferred embodiments of the present disclosure will now be described in detail.
[0011] The liquid crystalline polyester of this embodiment (hereinafter also simply referred to as "liquid crystalline polyester") is a liquid crystalline polyester having a peak position (G) calculated by formula (1) of 4.50 or more and 4.87 or less, and a log(M) value of the peak top of the molecular weight distribution curve of 5.05 or more.
number
number
[0012] The liquid crystal polyester of the present embodiment has good fluidity when melted, and the molded product has excellent mechanical properties (tensile strength, nominal tensile break strain). In addition, the liquid crystal polyester of the present embodiment has a high deflection temperature under load, and can be said to be a molding raw material that has moldability, mechanical properties, and heat resistance.
[0013] The present inventors have devised a peak position (G), which is a variable represented by formula (1), and have found that a liquid crystal polyester having good flowability when melted while having good mechanical properties and heat resistance can be obtained by setting the value of the peak position (G) and the value of the peak top within a specific range. It is considered that the inclusion of high molecular weight molecular chains in the liquid crystal polyester is preferable from the viewpoint of improving the mechanical properties and heat resistance of the liquid crystal polyester. It is considered that the inclusion of low molecular weight molecular chains in the liquid crystal polyester is preferable from the viewpoint of improving the fluidity of the liquid crystal polyester. The liquid crystal polyester of the present embodiment has a peak position (G) value and a peak top value in a specific range, and contains high molecular weight molecular chains and low molecular weight molecular chains in a well-balanced manner, and therefore is considered to exhibit the above-mentioned effects.
[0014] The above molecular weight distribution curve is a polystyrene-equivalent molecular weight distribution curve measured using GPC under the following conditions. <Preparation of measurement solution> Add 3.4 g of pentafluorophenol (PFP) to 4.86 mg of powdered sample by freeze-pulverization, and dissolve for 2 hours at 120-125°C while stirring with a stirrer. After cooling to 40-50°C, add 6.3 g of chloroform, stir, and then filter through a filter with a pore size of 0.45 μm to obtain a measurement solution. <Measurement conditions> GPC equipment: HLC-8420GPC (Tosoh) Column: TSKgel SuperHM-H (φ6.0mm x 150mm) (2 columns) Eluent: PFP / chloroform (weight ratio 35 / 65) Flow rate: 0.4mL / min Detector: RI detector Column temperature: 40℃ Injection volume: 20μL Molecular weight standards: Standard polystyrene
[0015] The above formula (2) is a formula for fitting the molecular weight distribution curve as the sum of two normal distributions. In the fitting, the parameters (A1, A2, μ1, μ2, σ1, and σ2) in formula (2) are determined so that the sum of squares of the difference in differential molecular weight distribution at each log(M) between the molecular weight distribution curve and formula (2) (sum of normal distributions) is minimized. The parameters are determined under the following conditions using the solver function of Microsoft (registered trademark) Excel (registered trademark). The initial values of the parameters are appropriately changed so that the sum of squares is minimized. <Software used> Microsoft(R) Excel(R) for Microsoft 365 MSO (Version 2209) <Solver conditions> Solution: GPG nonlinear Convergence: 0.0001 Derivative: Center
[0016] The peak position (G) is preferably 4.50 or more, more preferably 4.60 or more. The peak position (G) is preferably 4.87 or less, more preferably 4.85 or less.
[0017] The log(M) value of the peak top of the molecular weight distribution curve is 5.05 or more, preferably 5.06 or more, more preferably 5.07 or more. The log(M) value of the peak top of the molecular weight distribution curve may be, for example, 5.30 or less, or 5.20 or less.
[0018] The liquid crystal polyester may be any polyester that exhibits liquid crystallinity in a molten state. The liquid crystal polyester may be one type of polymer or a mixture of two or more types of polymers.
[0019] The liquid crystal polyester has a constituent unit (also called a monomer unit) derived from a raw material monomer. The liquid crystal polyester may have a main monomer unit (for example, 90 mol% or more, 95 mol% or more, or 99 mol% or more of the monomer units relative to the total of all monomer units, preferably all monomer units) that is derived from an aromatic compound. The liquid crystal polyester in which all monomer units are derived from an aromatic compound is also called a wholly aromatic liquid crystal polyester.
[0020] The liquid crystal polyester has a first monomer unit having a condensed aromatic ring and a monomer unit having a benzene ring. The liquid crystal polyester may have one or more types of the first monomer unit. The liquid crystal polyester may also have one or more types of the second monomer unit. The second monomer unit may be a monomer unit having a benzene ring and not having a condensed aromatic ring.
[0021] The first monomer unit may be a monomer unit derived from an aromatic compound (1) having a condensed aromatic ring, and the second monomer unit may be a monomer unit derived from an aromatic compound (2) having a benzene ring.
[0022] In this specification, the term "origin" means that in the monomer unit of the liquid crystal polyester formed by polymerization of the raw material monomer, the chemical structure of the functional group that contributes to polymerization of the raw material monomer has changed, but other structural changes have not occurred. The term "origin" here is a concept that also includes the case where the monomer is derived from a polymerizable derivative of the raw material monomer (for example, a compound obtained by converting the functional group that contributes to polymerization of the raw material monomer into another polymerizable group).
[0023] Examples of the first monomer unit include a monomer unit derived from an aromatic hydroxycarboxylic acid (1-1) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-1)), a monomer unit derived from an aromatic dicarboxylic acid (1-2) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-2)), and a monomer unit derived from an aromatic diol (1-3) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-3)).
[0024] Examples of the second monomer unit include a monomer unit derived from an aromatic hydroxycarboxylic acid (2-1) (hereinafter also referred to as a monomer unit (2-1)), a monomer unit derived from an aromatic dicarboxylic acid (2-2) (hereinafter also referred to as a monomer unit (2-2)), and a monomer unit derived from an aromatic diol (2-3) (hereinafter also referred to as a monomer unit (2-3)).
[0025] Examples of the fused aromatic ring contained in the first monomer unit include a naphthalene ring, an anthracene ring, a phenanthrene ring, a tetracene ring, a pyrene ring, a triphenylene ring, a perylene ring, and a fluorene ring. Among these, a naphthalene ring is preferred from the viewpoints of availability and cost.
[0026] Examples of the monomer units contained in the liquid crystal polyester include a monomer unit represented by the following formula (I) (hereinafter also referred to as monomer unit (I)), a monomer unit represented by the following formula (II) (hereinafter also referred to as monomer unit (II)), and a monomer unit represented by the following formula (III) (hereinafter also referred to as monomer unit (III)). -O-Ar1 -CO- (I) -CO-Ar 2 -CO- (II) -X-Ar 3 -Y- (III) [In the formula, Ar 1 , Ar 2 and Ar 3 each independently represents a phenylene group, a biphenylene group, a condensed polycyclic aromatic hydrocarbon group, or a group represented by formula (IV). 1 , Ar 2 and Ar 3 may be substituted with a halogen atom, an alkyl group or an aryl group. X and Y each independently represent an oxygen atom or an imino group (-NH-). -Ar 4 -Z-Ar 5 - (IV) [In the formula, Ar 4 and Ar 5 each independently represents a phenylene group or a condensed polycyclic aromatic hydrocarbon group; Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkanediyl group.
[0027] The phenylene group may be a 1,4-phenylene group or a 1,3-phenylene group, preferably a 1,4-phenylene group.
[0028] The biphenylene group may be a 4,4'-biphenylylene group.
[0029] The condensed polycyclic aromatic hydrocarbon group is a group in which two hydrogen atoms are removed from a condensed polycyclic aromatic hydrocarbon. Examples of the condensed polycyclic aromatic hydrocarbon include naphthalene, anthracene, phenanthrene, tetracene, pyrene, triphenylene, perylene, and fluorene. Among these, naphthalene is preferred from the viewpoints of availability and cost.
[0030] The condensed polycyclic aromatic hydrocarbon group may be a naphthylene group. The naphthylene group may be a 2,6-naphthylene group or a 2,7-naphthylene group, and is preferably a 2,6-naphthylene group.
[0031] Examples of the halogen atom as a substituent include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0032] The alkyl group as a substituent may be linear, branched or cyclic. The alkyl group may be, for example, an alkyl group having 1 to 10 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group.
[0033] The aryl group as a substituent may be a single ring or a condensed ring. The aryl group may be, for example, an aryl group having 6 to 20 carbon atoms. Examples of the aryl group include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group. The aryl group may be a group in which a hydrogen atom of an aromatic ring is substituted with an alkyl group, such as a tolyl group.
[0034] Ar 1 , Ar 2 and Ar 3 The number of substituents that the has may be, for example, 0 to 2, may be 0 or 1, or may be 0.
[0035] X and Y are preferably oxygen atoms.
[0036] The alkanediyl group in Z may be linear or branched. The alkanediyl group may be an alkanediyl group having 1 to 10 carbon atoms. Examples of the alkanediyl group include a methylene group, an ethanediyl group, a propanediyl group (e.g., a propane-2,2-diyl group), a butanediyl group, and an octanediyl group (e.g., an octane-3,3-diyl group).
[0037] Z is preferably an oxygen atom, a sulfur atom, a methylene group, an ethanediyl group, or a propanediyl group, and more preferably an oxygen atom.
[0038] The first monomer unit is a monomer unit represented by formula (I) (Ar 1 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5 at least one of which is a condensed polycyclic aromatic hydrocarbon group, may be a group represented by formula (IV), and the monomer unit represented by formula (II) (Ar 2 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5 at least one of which is a condensed polycyclic aromatic hydrocarbon group, a group represented by formula (IV); 2 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5 at least one of which is a condensed polycyclic aromatic hydrocarbon group represented by formula (IV).
[0039] The first monomer unit may be a monomer unit derived from an aromatic compound (1) having a condensed aromatic ring. Examples of the aromatic compound (1) include 2-hydroxy-6-naphthoic acid, 2,6-naphthalenedicarboxylic acid, 2,6-dihydroxynaphthalene, 2-hydroxy-3-naphthoic acid, 1-hydroxy-5-naphthoic acid, and 2,7-naphthalenediol.
[0040] The second monomer unit is a monomer unit represented by formula (I) (Ar 1 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5 is a phenylene group), and the monomer unit represented by formula (II) (Ar 2 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5is a phenylene group), and the monomer unit represented by formula (III) (Ar 3 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5 may be a group represented by formula (IV) in which R is a phenylene group.
[0041] The second monomer unit may be a monomer unit derived from an aromatic compound (2) having a benzene ring but no condensed aromatic ring. Examples of the aromatic compound (2) include p-hydroxybenzoic acid, terephthalic acid, hydroquinone, isophthalic acid, and 4,4'-biphenol.
[0042] In the liquid crystal polyester, the content of the first monomer unit may be, for example, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, based on the total of all monomer units constituting the liquid crystal polyester. When the content of the first monomer unit is high, the dielectric properties tend to be improved. In addition, the content of the first monomer unit may be, for example, 90 mol% or less, 85 mol% or less, or 80 mol% or less, based on the total of all monomer units constituting the liquid crystal polyester. This tends to improve moldability and processability at low temperatures. That is, the content of the first monomer unit may be, for example, 20 mol% or more and 90 mol% or less, 20 mol% or more and 85 mol% or less, 20 mol% or more and 80 mol% or less, 30 mol% or more and 90 mol% or less, 30 mol% or more and 85 mol% or less, 30 mol% or more and 80 mol% or less, 40 mol% or more and 40 mol% or less, 40 mol% or more and 85 mol% or less, 40 mol% or more and 80 mol% or less, 50 mol% or more and 90 mol% or less, 50 mol% or more and 85 mol% or less, 50 mol% or more and 80 mol% or less, 60 mol% or more and 90 mol% or less, 60 mol% or more and 85 mol% or less, 60 mol% or more and 80 mol% or less, 70 mol% or more and 90 mol% or less, 70 mol% or more and 85 mol% or less, or 70 mol% or more and 80 mol% or less.
[0043] In the liquid crystal polyester, the content of the second monomer unit may be, for example, 10 mol% or more, 15 mol% or more, or 20 mol% or more, based on the total of all monomer units constituting the liquid crystal polyester. This tends to be excellent in terms of cost. In addition, the content of the second monomer unit may be, for example, 80 mol% or less, 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, or 30 mol% or less, based on the total of all monomer units constituting the liquid crystal polyester. That is, the content of the second monomer unit may be, for example, 10 mol% or more and 80 mol% or less, 10 mol% or more and 70 mol% or less, 10 mol% or more and 60 mol% or less, 10 mol% or more and 50 mol% or less, 10 mol% or more and 40 mol% or less, 10 mol% or more and 30 mol% or less, 15 mol% or more and 80 mol% or less, 15 mol% or more and 70 mol% or less, 15 mol% or more and 60 mol% or less, 15 mol% or more and 50 mol% or less, 15 mol% or more and 40 mol% or less, 15 mol% or more and 30 mol% or less, 20 mol% or more and 80 mol% or less, 20 mol% or more and 70 mol% or less, 20 mol% or more and 60 mol% or less, 20 mol% or more and 50 mol% or less, 20 mol% or more and 40 mol% or less, or 20 mol% or more and 30 mol% or less.
[0044] In the liquid crystal polyester, the total amount of the first monomer unit and the second monomer unit may be, for example, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% relative to the sum of all monomer units constituting the liquid crystal polyester.
[0045] The liquid crystal polyester may be a polymer having two or more kinds of monomer units (I), or may be a polymer having monomer units (I), monomer units (II) and monomer units (III).
[0046] When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (I) may be, for example, 30 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, or 55 mol% or more, based on the total of all the monomer units of the liquid crystal polyester. When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (I) may be, for example, 80% or less, or 70% or less, based on the total of all the monomer units of the liquid crystal polyester. That is, when the liquid crystal polyester has monomer unit (I), monomer unit (II) and monomer unit (III), the content of monomer unit (I) may be, for example, 30 mol% or more and 80 mol% or less, 30 mol% or more and 70 mol% or less, 40 mol% or more and 80 mol% or less, 40 mol% or more and 70 mol% or less, 45 mol% or more and 80 mol% or less, 45 mol% or more and 70 mol% or less, 50 mol% or more and 80 mol% or less, 50 mol% or more and 70 mol% or less, 55 mol% or more and 80 mol% or less, or 55 mol% or more and 70 mol% or less.
[0047] When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (II) and the content of the monomer unit (III) may be, for example, 35 mol% or less, or 30 mol% or less, based on the total of all monomer units of the liquid crystal polyester. When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (II) and the content of the monomer unit (III) may be, for example, 5 mol% or more, 10 mol% or more, or 15 mol% or more, based on the total of all monomer units of the liquid crystal polyester. That is, when the liquid crystal polyester has monomer unit (I), monomer unit (II) and monomer unit (III), the content of monomer unit (II) and the content of monomer unit (III) may be, for example, 5 mol% or more and 35 mol% or less, 5 mol% or more and 30 mol% or less, 10 mol% or more and 35 mol% or less, 10 mol% or more and 30 mol% or less, 15 mol% or more and 35 mol% or less, or 15 mol% or more and 30 mol% or less, relative to the sum of all monomer units of the liquid crystal polyester.
[0048] The liquid crystal polyester may have monomer units other than the monomer unit (I), the monomer unit (II) and the monomer unit (III), and the number of such monomer units may be 10 mol % or less, 5 mol % or less, 2 mol % or less, or 1 mol % or less, or may be 0 mol % or less, relative to the total number of all monomer units of the liquid crystal polyester.
[0049] In this specification, the number of each monomer unit contained in the liquid crystal polyester is determined by the analysis method described in JP 2000-19168 A. Specifically, the liquid crystal polyester is depolymerized by reacting it with a lower alcohol in a supercritical state, and the depolymerization product (monomer that derives each monomer unit) is quantified by liquid chromatography, whereby the number of each monomer unit relative to the total monomer units can be calculated.
[0050] The liquid crystal polyester can be produced by polymerizing raw material monomers corresponding to the monomer units constituting the liquid crystal polyester, for example, according to the method described in Japanese Patent No. 6439027.
[0051] The dielectric loss tangent of the liquid crystal polyester at 10 GHz may be, for example, 0.002 or less, preferably 0.0015 or less, and more preferably 0.001 or less.
[0052] The liquid crystal polyester may have a relative dielectric constant at 10 GHz of, for example, 4.0 or less, or 3.8 or less. The liquid crystal polyester may have a relative dielectric constant at 10 GHz of, for example, 2.8 or more, or 3.0 or more.
[0053] In this specification, the dielectric loss tangent and the relative dielectric constant at 10 GHz of the liquid crystal polyester are measured by the following method. Using an injection molding machine (ROBOSHOT S-2000i 30B, manufactured by FANUC Corporation), a test piece having a width of 50 mm, a length of 50 mm, and a thickness of 0.5 mm is obtained using a liquid crystal polyester pellet as a molding material under the conditions of a mold temperature of 130°C and an injection speed of 50 mm / s. The cylinder temperature is set to a temperature (e.g., 300 to 350°C) at which the liquid crystal polyester melts and can be poured into the mold. The relative dielectric constant and dielectric loss tangent at 10 GHz of the obtained test piece are measured using a vector network analyzer (N5290A, manufactured by Keysight Technologies, Inc.) and a split cylinder resonator (CR710, manufactured by EM Lab Co., Ltd.). The measurement environment is set to 23°C and 50% RH.
[0054] The flow initiation temperature of the liquid crystal polyester may be, for example, 250° C. or more, or 270° C. or more. The flow initiation temperature of the liquid crystal polyester may be, for example, 400° C. or less, 360° C. or less, or 340° C. or less. That is, the flow initiation temperature of the liquid crystal polyester may be, for example, 250°C or more and 400°C or less, 250°C or more and 360°C or less, 250°C or more and 340°C or less, 270°C or more and 400°C or less, 270°C or more and 360°C or less, or 270°C or more and 340°C or less.
[0055] In this specification, the flow initiation temperature of the liquid crystal polyester is measured using a flow tester, and the liquid crystal polyester is subjected to a pressure of 9.8 MPa (100 kg / cm 2 ) while heating at a rate of 4°C / min under a load of 1000 g / s, and extruding the molten liquid crystalline polyester from a nozzle with an inner diameter of 1 mm and a length of 10 mm, the temperature at which it reaches a viscosity of 4800 Pa s (48,000 poise).
[0056] The number average molecular weight (Mn) of the liquid crystal polyester may be, for example, 35,000 or more, and from the viewpoint of more excellent mechanical properties and heat resistance, may be 37,000 or more, 39,000 or more, or 40,000 or more. The number average molecular weight (Mn) of the liquid crystal polyester may be, for example, 60,000 or less, and from the viewpoint of more excellent fluidity and flexibility, may be 58,000 or less, 56,000 or less, or 55,000 or less.
[0057] The weight average molecular weight (Mw) of the liquid crystal polyester may be, for example, 100,000 or more, and from the viewpoint of more excellent mechanical properties and heat resistance, may be 120,000 or more, 130,000 or more, or 140,000 or more. The weight average molecular weight (Mw) of the liquid crystal polyester may be, for example, 250,000 or less, and from the viewpoint of more excellent fluidity and flexibility, may be 230,000 or less, 220,000 or less, or 210,000 or less.
[0058] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the liquid crystal polyester may be, for example, 3.20 or more, and from the viewpoint of superior heat resistance, may be 3.25 or more, 3.30 or more, or 3.35 or more. The ratio (Mw / Mn) may be, for example, 3.96 or less, and from the viewpoint of superior fluidity, may be 3.95 or less, 3.94 or less, or 3.93 or less.
[0059] In this specification, the number average molecular weight (Mn), weight average molecular weight (Mw) and ratio (Mw / Mn) of the liquid crystal polyester are values determined from the above-mentioned molecular weight distribution curve.
[0060] The liquid crystal polyester may be one type of liquid crystal polyester or a mixture of two or more types of liquid crystal polyesters, for example, a mixture of two or more types of liquid crystal polyesters having different molecular weights.
[0061] The liquid crystal polyester may, for example, include a first liquid crystal polyester having a first molecular weight distribution curve and a second liquid crystal polyester having a second molecular weight distribution curve. At this time, the log(M) value of the peak top of the first molecular weight distribution curve may be smaller than the log(M) value of the peak top of the second molecular weight distribution curve. In addition, the content of the first liquid crystal polyester may be smaller than the content of the second liquid crystal polyester.
[0062] The liquid crystal polyester has good fluidity when melted, and the molded article has excellent mechanical properties. Therefore, the liquid crystal polyester can be suitably used as a molding material for obtaining a molded article. The liquid crystal polyester may be used, for example, as pellets.
[0063] The liquid crystal polyester may be mixed with other components to be used as a liquid crystal polyester composition.
[0064] The liquid crystal polyester composition may contain, for example, one or more resins other than the liquid crystal polyester, such as polyolefin, cyclic polyolefin, polyvinyl chloride, polysulfone, (meth)acrylic resin, polyphenylene ether resin, polyacetal resin, polyamide resin, imide resin, cellulose resin, polyether ether ketone resin, fluororesin, polycarbonate resin, styrene-based resin, and thermosetting resin.
[0065] The liquid crystal polyester composition may further contain an inorganic filler, a colorant, a dispersant, a plasticizer, an antioxidant, a curing agent, a flame retardant, a heat stabilizer, an ultraviolet absorber, an antistatic agent, a surfactant, a lubricant, a release agent, and the like.
[0066] The liquid crystal polyester composition has excellent fluidity when melted, and therefore can be suitably used as a molding material. The liquid crystal polyester composition may be used, for example, in the form of pellets.
[0067] The molded article of the present embodiment may be a molded article containing the above-mentioned liquid crystal polyester, or may be a molded article containing the above-mentioned liquid crystal polyester composition.The molded article of the present embodiment may be a connector, a socket, a relay part, a coil bobbin, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a household electrical appliance part, a lighting fixture part, an audio product part, an optical cable ferrule, a telephone part, a facsimile part, a modem part, a separation claw, a heater holder, an impeller, a fan gear, a gear, a bearing, a motor part, a motor case, an engine part, an engine room part, an electrical equipment part, an automobile interior part, a microwave cooking pot, a heat-resistant tableware, a floor material, a wall material, a beam, a column, a roof material, an aircraft part, a spacecraft part, a space equipment part, a nuclear reactor, an ocean facility member, a cleaning tool, an optical equipment part, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment part, a medical material, a sensor part, a sanitary equipment, a sporting goods, or a leisure goods.
[0068] The molded article of the present embodiment can be obtained, for example, by molding the liquid crystal polyester or liquid crystal polyester composition described above into a desired shape and subjecting it to processing treatment as necessary.
[0069] The molding method for the molded product is preferably melt molding, and examples of the melt molding method include injection molding, extrusion molding, compression molding, blow molding, vacuum molding, foam molding, and press molding.
[0070] Although the preferred embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments. EXAMPLES
[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, percentages and parts that represent the content or amount used are based on mass unless otherwise specified.
[0072] (Production Example 1) Production of Liquid Crystal Polyester (LCP1) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1035.0g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.3g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.1g (0.5 mol) of terephthalic acid, 255.2g of hydroquinone, 1226.87g (12 mol) of acetic anhydride, and 0.17g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C over 30 minutes under a nitrogen gas stream, and the temperature was maintained and refluxed for 1 hour. After that, the temperature was raised to 310°C over 4 hours and 35 minutes while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the obtained solid was 270°C. The obtained solid was cooled to room temperature and pulverized in a coarse pulverizer, and then heated from room temperature to 250°C over 1 hour in a nitrogen atmosphere, then heated from 250°C to 280°C over 5 hours, and held at 280°C for 6 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the obtained liquid crystal polyester (LCP1) was 301°C.
[0073] <Measurement of flow start temperature> Using a flow tester (Shimadzu Corporation, CFT-500 model), approximately 2 g of liquid crystal polyester pellets were filled into a cylinder equipped with a die having a nozzle with an inner diameter of 1 mm and a length of 10 mm, and the flow rate was measured at 9.8 MPa (100 kg / cm 2 The liquid crystal polyester was melted and extruded from the nozzle while heating at a rate of 4°C / min under a load of 1.5 g, and the temperature (FT) at which the viscosity reached 4800 Pa·s (48000 P) was measured and defined as the flow initiation temperature. "About 2 g" can be estimated as 2 g ± 0.1 g.
[0074] The dielectric constant of the crystalline polyester (LCP1) at 10 GHz was 3.5, and the dielectric loss tangent was 0.0010. The cylinder temperature during preparation of the test specimen was 320°C.
[0075] (Production Example 2) Production of Liquid Crystal Polyester (LCP2) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1035.0g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.3g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.1g (0.5 mol) of terephthalic acid, 255.2g of hydroquinone, 1226.87g (12 mol) of acetic anhydride, and 0.17g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C over 30 minutes under a nitrogen gas stream, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 310°C over 4 hours and 35 minutes while distilling off the by-product acetic acid. The reaction was deemed to have ended when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the resulting solid was 264°C. The resulting solid was cooled to room temperature and pulverized in a coarse pulverizer, then heated from room temperature to 250°C over 1 hour in a nitrogen atmosphere, then heated from 250°C to 292°C over 7 hours, and held at 292°C for 6 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the resulting liquid crystal polyester (LCP2) was 319°C.
[0076] The liquid crystal polyester (LCP2) had a relative dielectric constant of 3.6 and a dielectric loss tangent of 0.00091 at 10 GHz. The cylinder temperature during preparation of the test specimen was 320°C.
[0077] (Production Example 3) Production of Liquid Crystal Polyester (LCP3) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1035.0g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.3g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.1g (0.5 mol) of terephthalic acid, 255.2g of hydroquinone, 1226.87g (12 mol) of acetic anhydride, and 0.17g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C over 30 minutes under a nitrogen gas stream, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 310°C over 4 hours and 35 minutes while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the resulting solid was 270°C. The resulting solid was cooled to room temperature and crushed in a coarse crusher, then heated from room temperature to 250°C over 1 hour in a nitrogen atmosphere, then heated from 250°C to 306°C over 9 hours and 20 minutes, and held at 306°C for 6 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the resulting liquid crystal polyester (LCP3) was 330°C.
[0078] The liquid crystal polyester (LCP3) had a relative dielectric constant of 3.6 and a dielectric loss tangent of 0.00061 at 10 GHz. The cylinder temperature during preparation of the test specimen was 340°C.
[0079] (Production Example 4) Production of Liquid Crystal Polyester (LCP4) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1511.1 g (8.03 mol) of 2-hydroxy-6-naphthoic acid, 410.2 g (2.97 mol) of p-hydroxybenzoic acid, 1291.4 g (12.65 mol) of acetic anhydride, and 0.058 g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C under a nitrogen gas flow over 30 minutes, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 275°C over 4 hours while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the resulting solid was 217°C. The resulting solid was cooled to room temperature and pulverized in a coarse pulverizer, then heated from room temperature to 200°C over 1 hour in a nitrogen atmosphere, then heated from 200°C to 242°C over 7 hours, and held at 242°C for 10 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the resulting liquid crystal polyester (LCP4) was 292°C.
[0080] The liquid crystal polyester (LCP4) had a relative dielectric constant of 3.5 and a dielectric loss tangent of 0.0011 at 10 GHz. The cylinder temperature during preparation of the test specimen was 310°C.
[0081] (Production Example 5) Production of Liquid Crystal Polyester (LCP5) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1511.1 g (8.03 mol) of 2-hydroxy-6-naphthoic acid, 410.2 g (2.97 mol) of p-hydroxybenzoic acid, 1291.4 g (12.65 mol) of acetic anhydride, and 0.058 g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C under a nitrogen gas flow over 30 minutes, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 275°C over 4 hours while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the resulting solid was 217°C. The resulting solid was cooled to room temperature and pulverized in a coarse pulverizer, then heated from room temperature to 200°C over 1 hour in a nitrogen atmosphere, then heated from 200°C to 247°C over 7 hours and 50 minutes, and held at 247°C for 10 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the resulting liquid crystal polyester (LCP5) was 298°C.
[0082] The liquid crystal polyester (LCP5) had a relative dielectric constant of 3.5 and a dielectric loss tangent of 0.0011 at 10 GHz. The cylinder temperature during preparation of the test specimen was 330°C.
[0083] (Production Example 6) Production of Liquid Crystal Polyester (LCP6) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1511.1 g (8.03 mol) of 2-hydroxy-6-naphthoic acid, 410.2 g (2.97 mol) of p-hydroxybenzoic acid, 1291.4 g (12.65 mol) of acetic anhydride, and 0.058 g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C under a nitrogen gas flow over 30 minutes, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 275°C over 4 hours while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-initiating temperature of the resulting solid was 217°C. The resulting solid was cooled to room temperature and pulverized in a coarse pulverizer, then heated from room temperature to 200°C over 1 hour in a nitrogen atmosphere, then heated from 200°C to 259°C over 9 hours and 50 minutes, and held at 259°C for 10 hours, allowing the polymerization reaction to proceed in the solid phase. The flow-initiating temperature of the resulting liquid crystal polyester (LCP6) was 312°C.
[0084] The liquid crystal polyester (LCP6) had a relative dielectric constant of 3.6 and a dielectric loss tangent of 0.0010 at 10 GHz. The cylinder temperature during preparation of the test specimen was 345°C.
[0085] Example 1 (1) Manufacture of liquid crystal polyester and pellets The liquid crystalline polyester (LCP1) and the liquid crystalline polyester (LCP5) were mixed in a mass ratio of 60:40 to obtain the liquid crystalline polyester of Example 1. Next, the liquid crystalline polyester was granulated at a cylinder temperature of 320° C. using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystalline polyester.
[0086] (2) Evaluation of liquid crystal polyester and molded products The number average molecular weight (Mn) of the obtained liquid crystal polyester was 43,500, the weight average molecular weight (Mw) was 147,000, and the ratio (Mw / Mn) was 3.38. The molecular weight distribution curve of the liquid crystal polyester is as shown in Table 1, and the peak top position was log(M)=5.07. When the molecular weight distribution curve of the liquid crystal polyester was fitted with the above formula (2), A1 was 32.3, μ1 was 4.61, and σ1 was 1.01. 2 is 0.247, A2 is 63.4, μ2 is 5.13, σ2 2 was 0.133 and the peak position (G) was 4.78.
[0087] The melt viscosity, tensile strength, nominal tensile strain at break, relative dielectric constant, dielectric loss tangent, and deflection temperature under load were determined by the following methods. The results are shown in Table 1.
[0088] <Evaluation of fluidity when melted> Using a capillary rheometer (Capillograph 1D, manufactured by Toyo Seiki Seisakusho Co., Ltd.), a capillary with an inner diameter of 0.5 mm and a length of 10 mm was attached to the tip of the cylinder, and the pellets of the liquid crystal polyester were melted in the cylinder heated to 340° C. and extruded from the nozzle. The viscosity of the extruded liquid crystal polyester at a shear rate of 1000 / sec was measured, and the viscosity was evaluated as the melt viscosity of the liquid crystal polyester.
[0089] <Measurement of tensile strength and nominal tensile breaking strain> Using an injection molding machine (Nissei Plastic Industrial Co., Ltd., PNX-40-5A), liquid crystal polyester pellets were used as the molding material to injection mold ASTM D638 dumbbell-shaped test pieces Type IV (thickness 2.5 mm) under the conditions of cylinder temperature 330 ° C, mold temperature 130 ° C, and injection speed 75 mm / s. For each of the five samples of the obtained dumbbell test pieces, a tensile test was performed using a tensile tester (A & D Co., Ltd., Tensilon RTG-1310) with a chuck distance of 50 mm, a crosshead speed of 10 mm / min, and a test temperature of 25 ° C. The elongation at that time was measured, and the tensile strength at break (MPa) and the nominal tensile break strain (%) were calculated as the average values of the five samples. The nominal tensile breaking strain was calculated by the following formula: Nominal tensile breaking strain (%) = (L-Lo) / Lo x 100 Lo: Length of chuck distance before test (mm) L: Distance between chucks at break (mm)
[0090] <Evaluation of dielectric properties> Using an injection molding machine (FANUC Corporation, ROBOSHOT S-2000i 30B), a test piece with a width of 50 mm, a length of 50 mm, and a thickness of 0.5 mm was obtained using a liquid crystal polyester pellet as the molding material under the conditions of a cylinder temperature of 325°C, a mold temperature of 130°C, and an injection speed of 50 mm / s. The relative dielectric constant and dielectric loss tangent at 10 GHz of the obtained test piece were measured using a vector network analyzer (Keysight Technologies, Inc., N5290A) and a split cylinder resonator (EM Lab, Inc., CR710). Measurement environment: 23℃, 50% RH
[0091] <Evaluation of deflection temperature under load> Using an injection molding machine (Nissei Plastic Industrial Co., Ltd., PNX-40-5A), a rod-shaped molded product was produced in accordance with ASTM D648 using liquid crystal polyester pellets as the molding material under conditions of a cylinder temperature of 330°C, a mold temperature of 130°C, and an injection speed of 75 mm / s. The deflection temperature under load (DTUL(°C)) of the obtained rod-shaped molded product was measured in accordance with ASTM D648 at a load of 1.82 MPa and a heating rate of 2°C / min.
[0092] Example 2 The liquid crystal polyester (LCP1), the liquid crystal polyester (LCP3) and the liquid crystal polyester (LCP5) were mixed in a mass ratio of 50:10:40 to obtain a liquid crystal polyester of Example 2. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 1.
[0093] In Example 2, the cylinder temperature during granulation was 320°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 330°C, the cylinder temperature in <evaluation of dielectric properties> was 325°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 330°C.
[0094] Example 3 The liquid crystal polyester (LCP1) and the liquid crystal polyester (LCP6) were mixed in a mass ratio of 60:40 to obtain a liquid crystal polyester of Example 3. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 1.
[0095] In Example 3, the cylinder temperature during granulation was 325°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 330°C, the cylinder temperature in <evaluation of dielectric properties> was 325°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 330°C.
[0096] Example 4 The liquid crystal polyester (LCP1) and the liquid crystal polyester (LCP6) were mixed in a mass ratio of 80:20 to obtain the liquid crystal polyester of Example 4. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 1.
[0097] In Example 4, the cylinder temperature during granulation was 325°C, the cylinder temperature in <measurement of tensile strength and nominal tensile strain at break> was 330°C, the cylinder temperature in <evaluation of dielectric properties> was 325°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 330°C.
[0098] Comparative Example 1 The liquid crystal polyester (LCP2) and the liquid crystal polyester (LCP4) were mixed in a mass ratio of 60:40 to obtain a liquid crystal polyester of Comparative Example 1. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 2.
[0099] In Comparative Example 1, the cylinder temperature during granulation was 320°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 340°C, the cylinder temperature in <evaluation of dielectric properties> was 330°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 340°C.
[0100] Comparative Example 2 The liquid crystal polyester (LCP1) and the liquid crystal polyester (LCP5) were mixed in a mass ratio of 80:20 to obtain a liquid crystal polyester of Comparative Example 2. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 2.
[0101] In Comparative Example 2, the cylinder temperature during granulation was 320°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 320°C, the cylinder temperature in <evaluation of dielectric properties> was 330°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 320°C.
[0102] Comparative Example 3 Using only the liquid crystal polyester (LCP1), pellets were prepared, and the liquid crystal polyester and molded articles were evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0103] In Comparative Example 3, the cylinder temperature during granulation was 320°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 330°C, the cylinder temperature in <evaluation of dielectric properties> was 320°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 330°C.
[0104] Comparative Example 4 The liquid crystal polyester (LCP3) and the liquid crystal polyester (LCP5) were mixed in a mass ratio of 60:40 to obtain a liquid crystal polyester of Comparative Example 4. Using the obtained liquid crystal polyester, pellets were prepared in the same manner as in Example 1, and the liquid crystal polyester and molded articles were evaluated. The results are shown in Table 2.
[0105] In Comparative Example 4, the cylinder temperature during granulation was 340°C, the cylinder temperature in <measurement of tensile strength and nominal tensile break strain> was 330°C, the cylinder temperature in <evaluation of dielectric properties> was 330°C, and the cylinder temperature in <evaluation of deflection temperature under load> was 330°C.
[0106] [Table 1]
[0107] [Table 2]
[0108] Fig. 1 is a diagram showing the molecular weight distribution curve of Example 1. In Fig. 1, 10 indicates the molecular weight distribution curve, and 1, 2, and 3 indicate the first normal distribution, the second normal distribution, and the sum of these. In the above fitting, the molecular weight distribution curve 10 is fitted as the sum of the first normal distribution 1 and the second normal distribution 2.
Claims
1. The peak position (G) calculated by the formula (1) is 4.50 or more and 4.87 or less, A liquid crystal polyester having a peak top in a molecular weight distribution curve of 5.05 or more in terms of log(M) value. [0010] [In formula (1), A 1 , A 2 , μ 1 and μ 2 The molecular weight distribution curve measured by GPC (vertical axis: differential molecular weight distribution, horizontal axis: logarithm of molecular weight in polystyrene equivalent with base 10) is calculated by the following formula (2): 1 <μ 2 The values shown are those obtained by fitting as follows.] [0025] [In formula (2), M represents the molecular weight, and log(M) represents the logarithm of the molecular weight.]
2. 2. The liquid crystal polyester according to claim 1, wherein the peak top in the molecular weight distribution curve has a log(M) value of 5.05 or more and 5.30 or less.
3. A 1 <A 2 The liquid crystal polyester according to claim 1 ,
4. The liquid crystal polyester according to claim 1 , which has a weight average molecular weight (Mw) of 100,000 or more and 250,000 or less.
5. The liquid crystal polyester according to claim 1 , having a number average molecular weight (Mn) of 35,000 or more and 60,000 or less.
6. 2. The liquid crystal polyester according to claim 1, wherein the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 3.20 or more and 3.96 or less.
7. The liquid crystal polyester according to claim 1 , comprising a first monomer unit having a condensed aromatic ring and a second monomer unit having a benzene ring.
8. The liquid crystal polyester according to claim 7 , wherein the condensed aromatic ring is a naphthalene ring.
9. The liquid crystalline polyester of claim 1 comprising two or more liquid crystalline polyesters.
10. A first liquid crystal polyester having a first molecular weight distribution curve; a second liquid crystal polyester having a second molecular weight distribution curve; Including, the log(M) value of the peak top of the first molecular weight distribution curve is smaller than the log(M) value of the peak top of the second molecular weight distribution curve; The liquid crystal polyester according to claim 1 .
11. A method for producing the liquid crystal polyester according to any one of claims 1 to 10, comprising the steps of: A method for producing a liquid crystalline polyester, comprising a step of mixing two or more liquid crystalline polyesters.
12. the step of mixing a first liquid crystal polyester having a first molecular weight distribution curve and a second liquid crystal polyester having a second molecular weight distribution curve, the log(M) value of the peak top of the first molecular weight distribution curve is smaller than the log(M) value of the peak top of the second molecular weight distribution curve; The method of claim 11.
13. A pellet comprising the liquid crystal polyester according to any one of claims 1 to 10.
14. A molded article comprising the liquid crystal polyester according to any one of claims 1 to 10, The molded article is a connector, a socket, a relay part, a coil bobbin, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a home electrical appliance part, a lighting fixture part, an audio product part, a ferrule for an optical cable, a telephone part, a facsimile part, a modem part, a separation claw, a heater holder, an impeller, a fan gear, a gear, a bearing, a motor part, a motor case, an engine part, an engine room part, an electrical component part, an automobile interior part, a microwave cooking pot, a heat-resistant tableware, a flooring material, a wall material, a beam, a pillar, a roofing material, an aircraft part, a spacecraft part, a space equipment part, a nuclear reactor, an offshore facility member, a cleaning tool, an optical equipment part, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment part, a medical material, a sensor part, a sanitary fixture, a sporting goods, or a leisure goods.
Citation Information
Patent Citations
Liquid crystalline polymer composition
JP2003268252A